2002
DOI: 10.1021/jp013044i
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation Control in Solution Mediated Polymorphic Phase Transformations:  The Case of 2,6-Dihydroxybenzoic Acid

Abstract: This contribution describes the kinetics of the solution mediated phase transformation between forms 1 and 2 of dihydroxybenzoic acid. It is shown how a combination of kinetic, morphological, and modeling data can be used to give a full description of the rate-determining process in such a transformation. Surprisingly, secondary nucleation is found to dominate the kinetic processes. Such a phenomenon is well-known in continuous crystallization but is reported here for the first time in a polymorphic phase tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(151 citation statements)
references
References 13 publications
9
142
0
Order By: Relevance
“…Rodrigues-Hornedo et al studied the theophylline anhydrate-monohydrate system and found that anhydrous theophylline crystals acted as nucleation substrates for the monohydrate phase, followed by epitaxial growth of monohydrate crystals (23). Similar observations were reported by Davey et al who found that nucleation and epitaxial growth of polymorph 2 of dihydroxybenzoic acid took place on the surface of polymorph 1 crystals (24). If these findings are applied to the results presented here, the anhydrate crystals are able to act as nucleation substrates for the free base, while nucleation of the free base does not occur as readily on the monohydrate crystals.…”
Section: Solubilities Of Siramesine-hcl Anhydrate and Monohydratesupporting
confidence: 58%
“…Rodrigues-Hornedo et al studied the theophylline anhydrate-monohydrate system and found that anhydrous theophylline crystals acted as nucleation substrates for the monohydrate phase, followed by epitaxial growth of monohydrate crystals (23). Similar observations were reported by Davey et al who found that nucleation and epitaxial growth of polymorph 2 of dihydroxybenzoic acid took place on the surface of polymorph 1 crystals (24). If these findings are applied to the results presented here, the anhydrate crystals are able to act as nucleation substrates for the free base, while nucleation of the free base does not occur as readily on the monohydrate crystals.…”
Section: Solubilities Of Siramesine-hcl Anhydrate and Monohydratesupporting
confidence: 58%
“…It is interesting to note that higher water content in the solvents leads to shorter transformation time and ultimately the direct crystallization of monohydrate form. With the content of acetone in the solvent mixture increasing, more water molecules are surrounded by acetone molecules, which results in less water molecules to participate in the transformation from L-phenylalanine molecules to their hydrated ones (Davey et al, 2002).…”
Section: Solvent-mediated Transformationmentioning
confidence: 99%
“…Both the thermodynamic driving force and the kinetic factors may be affected by temperature. According to the authors' knowledge, for all the published work so far, the limiting step of the phase transformation is the nucleation and growth of the hydrate crystals (4,25,26). This also includes the compounds studied in the present work, carbamazepine and piroxicam.…”
Section: Kinetics Of the Solvent-mediated Anhydrateto-hydrate Phase Tmentioning
confidence: 91%